Maharashtra The Place - (:unkn) unknown (My University, 2022)
“Maharashtra” means “great land”, and it has lived up to its name in the past. It was a part of the Ashokan empire in the 2nd century BC. It was subsequently ruled by the Satavahana dynasty, the Chalukyas, the Rashtrakuts, and the Hoysalas. The Hoysalas soon crumbled against the incessant invasions by Alauddin Khilji which began in 1296. The Mughals were never able to completely conquer Maharashtra because of a man who was “diminutive in size but the tallest in stature”, Shivaji Raje Bhosale, who was famously known as Chhatrapati Shivaji Maharaj (Kuberch. 3).Once India became a colony of the British empire, Maharashtra came to be a part of the Bombay Presidency and was governed by the Governor-General of India. It was not until 1st May 1960, that the state of Maharashtra was formed. The landscape of Maharashtra can be physiologically divided into the Konkan Coastal Plane, Western Ghats, and Deccan Plateau. At the east of the Sahyadri, lies the Deccan Plateau, which covers from north to south- the Satpura range, Tapi valley, Ajantha range, Godavari valley, Harischandragad-Ahmednagar-Manjra Plateau, Bhima basin, Mahadeo range, and Krishna basin. The rivers in Maharashtra can be categorized into east-flowing rivers that drain into the Bay of Bengal and west-flowing rivers that drain into the Arabian Sea. The climate of Maharashtra is tropical. The major crops of Maharashtra can be divided into five agricultural regions, namely, rice, oilseeds, bajra, jowar, and cotton, as done by V. S. Datye and Amit Dhorde. With the rise of industries in Maharashtra, the role of agriculture in the state’s economy has declined extensively. Some industries that have proliferated in Maharashtra are sugarcane, cotton textile, chemicals, and electronics. Although Maharashtra’s economic growth is rapidly increasing, the growth is centered only on the major cities, namely, Mumbai, Pune, and Nagpur. There is a sharp increase in immigrants from rural to urban spaces, in search of employment and better living conditions. Maharashtra is thus still a “great land”, offering various opportunities to its citizens and allowing its inhabitants to dream big.
Keywords: Maharashtra The Place; Chatrapati Shivaji; Bombay Presidency; Deccan Plateau; Satavahanas; Chalukyas; Krishna River; Godavari River; Sahyadri; Marathi